The Influence of Learning and Development on HR Performance with Employee Engagement as a Mediating Variable: A Study in the Service Sector - Budi Wahono; Sopiah Sopiah; Ludi Wishnu Wardhana (Harmony Management: International Journal of Management Science and Business, 2025)
Human resource development through Learning and Development (L&D) is a major challenge in improving employee performance in the service sector that is highly dependent on service quality. However, the mechanism of L&D's influence on HR performance involving employee engagement as a mediating variable is still not comprehensively understood. This study aims to analyze the influence of L&D on HR performance with employee engagement as a mediator in service companies in Jakarta. The method used is a quantitative survey with data collection through questionnaires to 120 employees, and data analysis using AMOS-based Structural Equation Modeling (SEM). The results of the study indicate that L&D has a direct positive effect on HR performance and indirectly through increasing employee engagement, which acts as a significant mediator. This finding strengthens the theory of social learning and employee engagement and emphasizes the importance of integrating psychological aspects in employee development. The practical implication is that service sector management needs to design L&D programs that not only improve technical competence but also motivate employee engagement to maximize organizational performance. This study provides a relevant empirical contribution to the development of HR management theory and practice in the service sector.